2020
DOI: 10.22146/jtbb.43381
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Above Ground Carbon Sequestration in Trembesi (<i>Albizia saman</i>) and Johar (<i>Senna siamea</i>) at PT Multi Harapan Utama, East Kalimantan

Abstract: The open-pit mining method has a very large ecological impact. It causes the loss of forest vegetation which decreases CO2 absorption. Measuring the amount of carbon stored in plant biomass can represent the amount of CO2 that can be absorbed in the atmosphere. The objective of this research is to determine the carbon sequestration of Albizia saman and Senna siamea in different age classes at PT MHU Busang Jonggon Block, Kukar, East Kalimantan. Estimation of carbon sequestration in the stands of A. saman and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These values are comparably larger than those reported by Tandug (2006), 66.1Mg C ha -1 for F. moluccana plantations of ages 5-25 years old. However, compared to other plantation species such as Samanea saman, the C stored in F. moluccana is comparatively lower (314.28Mg /ha, which appears at six years old), and the lowest value was 193.31Mg/ha) (Fajariani et al, 2020).…”
Section: Carbon Stockmentioning
confidence: 74%
“…These values are comparably larger than those reported by Tandug (2006), 66.1Mg C ha -1 for F. moluccana plantations of ages 5-25 years old. However, compared to other plantation species such as Samanea saman, the C stored in F. moluccana is comparatively lower (314.28Mg /ha, which appears at six years old), and the lowest value was 193.31Mg/ha) (Fajariani et al, 2020).…”
Section: Carbon Stockmentioning
confidence: 74%
“…Because of their ability to absorb carbon, plants in this family can be used as shade in the environment. For example, a six-year-old stand S. saman can store carbon up to 314.28 tons/ha, while S. siamea can store 113.65 tons/ha in a nine-year-old stand (Fajariani et al 2020) Plant composition and abundance influence the stability of vegetation communities (Isbell et al 2009). The results of the diversity index calculation showed that the vegetation community in the studied area was in a stable state.…”
Section: Floramentioning
confidence: 99%